The role of culture in advancing sustainable energy policy and practice. (August 2022) - Goggins, Gary; Rau, Henrike; Moran, Paul; Fahy, Frances; Goggins, Jamie
Abstract: This paper offers a culturally sensitive analysis of measures to improve the energy performance of households. Comparing and combining insights from two recent sustainable energy initiatives in Ireland, we show how integrated approaches that work with participants' everyday practices and their links with people and place can yield substantial and sustained reductions in household energy use. Recognizing the centrality of culturally rooted meanings related to domestic energy use and the services it provides, our analysis challenges approaches to energy saving that overemphasize technology use and individual-level behavior change. Instead, it treats domestic energy use as an inherently social phenomenon that reflects place-specific cultural practices and material conditions. The paper also provides important lessons for upscaling and diffusion of good practice that recognize the centrality of formal and informal community networks and related aspects of trust in local social relations. Involving local advocates with strong social awareness and (inter-)cultural competences can increase engagement in community-based initiatives and deliver more sustainable results. Overall, the paper addresses a major energy policy challenge that has generated intense public debate, namely how to design and implement sustainable energy initiatives that meet the needs of participants and deliver lasting reductions in domestic energy use. Highlights: Offers culturally informed analysis of measures to improve household energy performance. Shows how practice-based approaches can result in reductions in energy use. Challenges techno-centric approaches that focus on individual-level behavior change. Provides important lessons for upscaling and diffusion of good practice. Demonstrates how to design sustainable energy initiatives that meet social needs.